The mere presence of a goalkeeper affects the accuracy of penalty kicks - Navarro, M.; van der Kamp, J.; Ranvaud, R.; Savelsbergh, G. J. P. (Journal of Sports Sciences, 2013)
The keeper-independent strategy, in which a football penalty kicker selects a target location in advance and ignores the goalkeeper's actions during the run-up, has been suggested to be the preferable strategy for taking a penalty kick. The current in-field experiment investigated the question of whether the goalkeeper can indeed be ignored. Ten intermediate-level football players were instructed to adopt a goalkeeper-independent strategy and to perform penalty kicks directed at one of two targets located in the upper corners of the goal under three conditions: without a goalkeeper, in the presence of a goalkeeper (who tried to save the ball), and in the presence of a goalkeeper who was informed by the penalty kickers where they intended to direct the ball. The mere presence of a goalkeeper impaired shot accuracy. The shots were more centralised, that is, biased toward the goalkeeper. The effects were enhanced for the condition in which the penalty kicker knew the goalkeeper was knowledgeable about ball direction. The findings were consistent with the response activation model that holds that aiming at a target can be biased toward salient visual non-targets. The implications for adopting and practising goalkeeper-independent strategies are discussed.